2018
DOI: 10.1111/tpj.13908
|View full text |Cite
|
Sign up to set email alerts
|

Host‐ and stage‐dependent secretome of the arbuscular mycorrhizal fungus Rhizophagus irregularis

Abstract: Arbuscular mycorrhizal fungi form the most wide-spread endosymbiosis with plants. There is very little host specificity in this interaction, however host preferences as well as varying symbiotic efficiencies have been observed. We hypothesize that secreted proteins (SPs) may act as fungal effectors to control symbiotic efficiency in a host-dependent manner. Therefore, we studied whether arbuscular mycorrhizal (AM) fungi adjust their secretome in a host- and stage-dependent manner to contribute to their extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
188
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(191 citation statements)
references
References 63 publications
3
188
0
Order By: Relevance
“…To identify which SWEET genes may be involved in AM symbiosis, we determined the expression patterns of all SWEET genes in M. truncatula roots inoculated with the AM fungus R. irregularis. First, we analysed RNA-seq transcriptome data of cortical cells containing arbuscules and cortical cells adjacent to hyphae, which were isolated by laser microdissection (Zeng et al, 2018). This analysis showed that of all the SWEET genes, only MtSWEET1b (Medtr3g089125) has high expression in root cells that are in contact with the fungus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To identify which SWEET genes may be involved in AM symbiosis, we determined the expression patterns of all SWEET genes in M. truncatula roots inoculated with the AM fungus R. irregularis. First, we analysed RNA-seq transcriptome data of cortical cells containing arbuscules and cortical cells adjacent to hyphae, which were isolated by laser microdissection (Zeng et al, 2018). This analysis showed that of all the SWEET genes, only MtSWEET1b (Medtr3g089125) has high expression in root cells that are in contact with the fungus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters used for mapping and TPM (transcripts per million; Wagner et al ., ) calculation are described in Zeng et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…RNA sequencing (RNAseq) data were collected from the following databases: NCBI gene expression omnibus http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE99655 for data from Medicago , chives, and Nicotiana benthamiana as well as laser microdissected ARBs and IRM; extraradical mycelium (ERM) and germinating spores from DDBJ database DRA002591; Lotus japonicus and tomato from DDBJ database DRA005187. RNAseq data were analysed as described by Zeng et al (). Quantification was done using default setting in CLC G enomics W orkbench 10.0.1.…”
Section: Methodsmentioning
confidence: 99%